2010
DOI: 10.1093/jscr/2010.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Pneumomediastinum after cocaine use: an unusual aetiology

Abstract: We describe an interesting case of pneumomediastinum secondary to cocaine abuse. The patient presented with severe chest pain following nasal inhalation of a large quantity of cocaine. Investigations revealed no chest injury; however oesophagitis was proven leading to a possible aetiology of oesophageal microperforation. After conservative management there was spontaneous resolution of the pneumomediastinum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…PM is part of the differential diagnosis for chest pain, particularly in young people, smokers, and drug abusers. The differential diagnosis of cocaine-induced chest pain includes PM, pneumothorax, pneumopericardium, aortic dissection, pulmonary hemorrhage, acute coronary syndrome, and coronary artery vasospasm [9]. The clinical history, the physical examination, the hemodynamic stability and the lack of blood analysis alterations are essential to exclude other alternative causes.…”
Section: Discussionmentioning
confidence: 99%
“…PM is part of the differential diagnosis for chest pain, particularly in young people, smokers, and drug abusers. The differential diagnosis of cocaine-induced chest pain includes PM, pneumothorax, pneumopericardium, aortic dissection, pulmonary hemorrhage, acute coronary syndrome, and coronary artery vasospasm [9]. The clinical history, the physical examination, the hemodynamic stability and the lack of blood analysis alterations are essential to exclude other alternative causes.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 It is now recognised that a similar presentation can occur following intranasal cocaine insufflation. 5,6 A Brazilian multicentre study demonstrated multiple pulmonary changes on CT related to cocaine use, with the majority of the participants cocaine smokers, but also included patients with intranasal cocaine use. 7 A Spanish case series looking at 46 patients with 'spontaneous' pneumomediastinum found that 26 of the patients had used cocaine prior to developing their symptoms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The presenting features of pneumomediastinum secondary to intranasal cocaine use are most commonly chest pain, 5,6 often described as pleuritic in nature, [11][12][13] and/or dyspnoea. [13][14][15] These features may present without tachycardia.…”
Section: Presentationmentioning
confidence: 99%
See 2 more Smart Citations